Upaya Meningkatkan Partisipasi Pemilih Melalui Literasi Politik Berbasis Digital Pada Pemilihan Umum di Kabupaten Karangasem - I Gede Suwenda Suwenda; Nyoman Diah Utari Dewi (Journal of Contemporary Public Administration, 2024)
Political Literacy is knowledge and understanding of political processes and political issues to be able to effectively carry out their role as citizens. Digital-based political literacy has a role in improving the quality of people's opinions and choices to participate in general elections. However, it still appears that not all people use social media for political literacy and the internet network is not adequate so that not all people participate in general elections. The conditions above are the background for this research to find out how to increase voter participation through digital-based political literacy in the General Election in Karangasem Regency as well as the obstacles and efforts to increase voter participation in the general election in Karangasem Regency. This research uses a qualitative descriptive method approach. The aim of the research is to find out and analyze increasing voter participation through digital-based political literacy in the General Election in Karangasem Regency as well as the obstacles and efforts. The research results show that increasing voter participation through digital-based political literacy in the General Election in Karangasem Regency seen from the indicators of need for political information, information communication movements and product evaluation of the final political process is optimal, but the search strategy indicators are not fully optimal. The obstacle is that not all voters take advantage of digital-based political literacy, there are still areas where internet networks are inadequate. The efforts used are to improve internet networks in blank spot areas, create innovations that can attract attention and provide education to the public through social media owned by election organizers, the government and political parties.